Imperial Overstretch: Germany in Soviet Policy from Stalin to Gorbachev : An Analysis Based on New Archival Evidence, Memoirs, and Interviews - Adomeit, Hannes 1942-2022 (Internationale Politik und Sicherheit, 2016)
The book is an analysis of the rise and fall of the Soviet empire in what, during the Cold War, was called ‘Eastern Europe’. Its central focus is the role played by the German problem in that process